APPLICATION SERVICES IN POLI GIZI RS. PELNI "PETAMBURAN" USING THE MICROSOFT VISUAL BASIC 6.0. - Dodi Rahman (Jurnal Sistem Informasi, 2005)
Scientific writing is about how to make the application of nutrition services with poly using Visual Basic 6.0. In scientific writing database is used also by using the Visual Data Manager program (VisData) which has been integrated in Visual Basic 6.0 program itself and the use of Crystal Reports 8.5 to display the report be printed. Scientific writing is also equipped with a hierarchical view and the flowchart of the program that created the application. This application displays the main menu which provides the names of diseases Diit, view daily food rations, the food must be in abstinence and examples of daily menus. This application is created aims to help a nutritionist in consultation service to patients quickly and accurately. With this program the service to patients can be further improved.